PREPARATION AND CHARACTERIZATION OF SOME NITROFURANTOIN METAL COMPLEXES (Sciences & Technology. A, exactes sciences, 2004)
The synthesis and characterization of two types of complexes fornitrofurantoin of the formula [M(NFD)Cl2]Cl and [M2(NFD)2Cl2]Cl4(Where M=Ti(III), Cr (III) and Fe(III), NFD = nitrofurantoin) weredescribed.They had been characterized by their elemental analysis, molarconductances, infrared and electronic spectra. The ligand exhibitedtetradentate manner, in both types, to form with two chloride ions the mostprobable octahedral geometry around the trivalent ions.